Letting the sun shine in at the WTO: How transparency brings the trading system to life - Robert Wolfe (World Trade Organization (WTO), 2013)
Without transparency, trade agreements are just words on paper. Transparency as disclosure allows economic actors and trading partners to see how rules are implanted; transparency in decision-making ensures fairness and peer review. In the first section of this paper, I discuss the logic of transparency in general and the motivation for its use in the trading system. Considerable information on WTO transparency mechanisms is available in the Minutes and annual reports of the various WTO bodies, and in the Director-General's annual overview of the trading system, but comparative analysis is not easy. In the second section, therefore, I develop a framework in which different transparency mechanisms can be compared to each other using the metaphor of three generations in the evolution of transparency in the trading system as a means of explaining how transparency works in the WTO. For sunshine to work, at least two things must happen. Information must be made available, and Members have to use it. Probing the extent to which Members comply with their notification obligations, in the third section, and their efforts to improve the notification process, allow an assessment of their commitment to being transparent. In the fourth section I consider how WTO committees are used to ensure that Members are accountable for their commitments, including to notify. Since the committees differ, I use the metaphor of the great pyramid of the legal order to compare committees to each other. Assessment of whether these mechanisms work underpins observations in the conclusion on whether more sunshine is needed, and efforts underway to improve existing mechanisms.
Keywords: F53; F55; K33; 330; international agreements; transparency; accountability; disclosure; decision-making; notification; peer review; surveillance